2004
DOI: 10.1097/00008571-200403000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptional expresi??n of the polymorphic myxovirus resistance protein A in response to interferon-alpha treatment

Abstract: Levels of myxovirus resistance protein A (MxA) mRNA were studied for a single nucleotide polymorphism in the promoter region at nucleotide position -88 of the gene to identify individual-specific responses to interferon (IFN)-alpha2 that might predict responsiveness to IFN-alpha therapy. We quantified MxA expression by reverse transcription and real-time polymerase chain reaction in peripheral blood mononuclear cells (PBMC) in vitro, induced by IFN-alpha2, from 22 healthy donors, in relation with G/T polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It significantly affects the induction of MxA mRNA expression. Carriers of GT or TT genotype display a markedly higher induction of MxA mRNA levels than those of GG genotype (Fernandez‐Arcas et al ., 2004). In this study, MxA –88 G/T was associated with the natural history of HBV infection with the TT genotype or T allele favourable for the recovery of HBV infection, and the GG genotype or G allele predominant in patients with persistent HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It significantly affects the induction of MxA mRNA expression. Carriers of GT or TT genotype display a markedly higher induction of MxA mRNA levels than those of GG genotype (Fernandez‐Arcas et al ., 2004). In this study, MxA –88 G/T was associated with the natural history of HBV infection with the TT genotype or T allele favourable for the recovery of HBV infection, and the GG genotype or G allele predominant in patients with persistent HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…GG genotype was found more frequently in non-responders of IFN treatment in hepatitis C, and a luciferase reporter assay revealed that the MxA promoter sequence of G haplotype had lower promoter activity than that of T haplotype [31]. Recently, Arcas et al [32] reported that GG genotype expressed lower amount of MxA mRNA than GT or TT genotype in IFN-treated peripheral blood mononuclear cells in vitro. Spiegel et al [15] reported that SARS-CoV replication was not affected in Vero E6 cells that were stably expressing MxA.…”
Section: Discussionmentioning
confidence: 99%
“…In case in whom peripheral immune cells express a higher level of MxA, MxA may induce amelioration of MS by enhancing the apoptosis of these immune cells. Recently, Gniadek et al [11] described a study of enhanced apoptosis of peripheral immune cells by IFN-β therapy, and Fernandez-Arcas et al [12] showed higher induction of MxA mRNA by IFN-α 2 in peripheral blood mononuclear cells in patients with − 88T allele than in those with − 88G allele. These interesting studies support the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%